Development of a Korean Hyperthyroidism-Specific Health Status Scale - Soongyo YEOUM; Sunah PARK (Tehran University of Medical Sciences, 2019)
Background: The aims of this study were to develop a hyperthyroidism-specific health status scale of Korea (K-HHSS) and to verify its validity and reliability. Methods: A methodological study was performed with hyperthyroid patients to assess the following properties: content validity, item analysis, Cronbach's α, intraclass correlation coefficients, and confirmatory factor analysis. The data were obtained from 80 patients with hyperthyroidism given medical care at C university hospital in Seoul in 2017. Results: The construct validity was supported by the item-analysis correlations ranging between 0.31 and 0.82. The internal consistency reliability was from 0.70 to 0.85, and the scale's stability was confirmed by intraclass correlation coefficients between 0.57 and 0.97. Construct reliability was 0.81 and the average variance extracted (AVE) was 0.72. These inclusion criteria resulted in the selection of 30 items in 7 categories. Conclusion: This scale will be useful as a limited health-measuring index for the nursing assessment of patients with hyperthyroidism in Korea.